Acetaminophen Analysis in Different Commercial Formulation of Iranian Acetaminophen Tablets: Iranian Acetaminophen tablet analysis - Talaie, Haleh; Sistanizad, Mohammad; H. Shirazi, Farshad; Kazeminia, Neda; Kayal, Ideh Baradaran (Iranian Journal of Pharmaceutical Sciences, 2018)
Acetaminophen is one of the most important antipyretic and analgesic drugs. It has an excellent efficacy when it is used in therapeutic doses, but in unsafe doses it can be resulted in hepatotoxicity and permanent liver failure. Due to disparities that have been reported between the actual and stated concentration of acetaminophen tablets, we aimed to compare the actual quantity of 8 Iranian generic acetaminophen tablets with the stated amount on the label, using HPLC method. Drug concentration has been measured by HPLC. We performed USP procedure for all models such as tablets, capsule, and oral solution assay preparations USP-36 NF31 by standard preparations. Method validation was achieved. For USP guidelines performance we need to concern on standard references. By chromatography equipment, we used HPLC analyzer 1200 degasser, 1200 bin pump, 1200 ALS, and 1200 VWD. Acetaminophen sample solution included 325 mg weighted quantity of the powder that transferred to a 200 ml volumetric flask in addition to 100 ml of mobile phase. A part of this solution was transferred throughout a 0.5 micrometer permeable filter (or finer). By injecting 10 μL of standard solution into the chromatograph, major peaks are measured as a response. As a final point, calculation of the quantity of acetaminophen in each brand was obtained via specific formula. According to the USP, all brands consisted of 90.0– 110.0 % of the labeled amount of active ingredient (p<0.05). Consequently, The USP standards are met for drugs with different lot numbers by a variety of companies. The differences of clinical attributes of Paracetamol overdose between Iran and other countries may be related to pharmacokinetic and pharmacodynamics issues, metabolism, genetic factors or environmental effects. Further studies are recommended.